Technical Study of the Implementation Method for Lightweight Brick Wall Construction: Analysis of Cost, Time, and Quality in Building Construction Projects - Mutia Ramadhany; Aulia Choiri Windari (Journal of Global Engineering Research and Science, 2026)
The construction of lightweight masonry walls plays a crucial role in supporting building stability, aesthetics, and comfort. This study aims to analyze the implementation methods of lightweight masonry walls in terms of cost, time, and quality in the Sky House Alam Sutera project. The research uses a descriptive-analytical approach with case study and literature review, involving field observation, interviews, technical documentation, and analysis of the project Budget Plan (BoQ) and technical standards. The results indicate that the material requirements per floor include 84,000 lightweight bricks, 60 sacks of cement, and 36 m³ of sand, with an estimated total cost of approximately IDR 260 million, including labor and overhead. The deployment of five parallel work teams allows wall installation per floor to be completed in about 28 days, including finishing, quality inspection, and curing. The use of thin bed mortar increases installation efficiency while maintaining proper thickness and alignment. Consistent quality control through visual inspection, compressive testing, and daily documentation ensures compliance with technical standards. The study emphasizes careful planning, labor coordination, and strict quality supervision to achieve efficiency in cost, time, and quality in multi-story building projects.